1.7 μm Tm-doped continue-wave and pulse fibre laser using a modulated pump based on variable pulse generated mechanisms. (November 2020) - He, Zhenxing; Zhang, Peng; Wu, Di; Wu, Xiaojie; He, Shuang; Wei, Jia; Gong, Xiyu; Li, Xiaoyan; Wang, Tong; Han, Kexuan; Tong, Shoufeng
Highlights: A 1.7 μm CW and pulse Tm-doped fiber laser is proposed and demonstrated. Variable pulse generated mechanisms can be achieved by a modulated pump. The laser had a high SMSR of 59 dB and a 3 dB linewidth of 0.18 nm. The range of repetition rate can be switched from kHz to dozens of MHz. Abstract: A 1.7 μm Tm-doped continue-wave and pulse fiber laser based on variable pulse generated mechanisms is proposed and experimentally demonstrated. The modulated pump was used to generate pulses in the cavity by switching mechanisms easily (gain-switched, self-saturable absorber and active mode-locking via pump modulation (AMPM)). In the laser scheme, a 1.55 μm amplified optically modulated signal generator was used as a homemade pump, including a semiconductor laser, a pulse signal driver and an erbium-doped fiber amplifier (EDFA). A 3-m long thulium-doped fiber (TDF) was pumped to obtained gain which covered 1.7 µm band. A Fiber Bragg Grating (FBG) is employed as a spectrum filter. Using the proposed scheme, we achieved the laser with a central wavelength of 1727.92 nm. The laser had a high Side-Mode Suppression Ratio (SMSR) of 59 dB and a 3 dB linewidth of 0.18 nm. Additionally, we modulated the pump, and the pulse train with a repetition rate from 10 kHz to100 kHz based on gain-switched mechanism was obtained. Aim to increase the repetition rate, the generation of self-mode-locked pulses with a repetition rate of 11.39 MHz was observed associating with a self-saturable absorber using a CW pump. Moreover, We adjusted the modulated frequency of pump to match with the free spectral range of the cavity, the pulse train with repetition rate of 11.39 MHz was obtained with higher signal power based on AMPM, and the serval order harmonic mode-locking states with repetition rate from 22.78 MHz to 45.56 MHz were demonstrated with the appropriate pump frequency.